How does studying rurally affect peer networks and resilience? A social network analysis of rural‐ and urban‐based students. (19th November 2018) - Burgis‐Kasthala, Sarath; Elmitt, Nicholas; Moore, Malcolm
Abstract: Objective: To examine differences in peer networks between urban‐based students and rural‐stream students in an Australian medical school and to examine how characteristics of networks relate to resilience. Design: Cross‐sectional survey asking students to signify social, academic and support relationships with students in the same year and to complete a survey on their resilience. Setting and participants: All second‐, third‐ and fourth‐year students at the Australian National University Medical School. Main outcome measures: Social network analysis comparing peer networks, t ‐test comparing mean resilience of urban and rural students. Results: A visual analysis of the peer networks of year 2, 3 and 4 medical students suggests greater integration of rural‐stream students within the year 2 and 4 urban cohorts. Resilience is similar between year 2 and 3 students in both urban and rural streams, but is significantly higher in year 4 rural‐stream students, compared to their urban‐based peers. Networks of rural‐stream students suggest key differences between their period spent rurally and on their return and integration within the larger student cohort. Furthermore, rural students, once reintegrated, had larger and stronger social networks than their urban counterparts. Conclusion: The results of the study suggest that the rural experience can instruct support systems in urban settings. However, whether the rural placement creates a more resilient student or resilient students are selected for rural placement is unclear.